Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengunjung di Suban Air Panas Kabupaten Rejang Lebong - Lara Ayu Lestari; Augustin Rina Herawati; Tri Yuniningsih; Teuku Afrizal (Universitas Negeri Medan, 2021)
This article aims to investigate the effect of service quality on visitor satisfaction in hot spring tourism areas. The concept of Servqual Parasuraman (quality of service) in 1998 was applied with aspects of responsiveness, reliability, empathy, assurance, and tangibles. This quantitative research was conducted at the Suban Hot Spring Baths, Rejang Lebong Regency. For primary data, the survey method was conducted on 100 respondents from 501 visitors to the Suban Hot Springs Bath in April 2021. Respondents were determined through accidental sampling technique. The survey method uses a closed questionnaire instrument on a Likert scale of 1-5. Secondary data sourced from the official web documentation of the Rejang Lebong Regency Tourism Office. Data analysis using SPSS 16 program with the hypothesis tested using the product moment by looking at the normality and linearity tests. The results of the study found that there was a significant influence between service quality and visitor satisfaction. Almost all aspects tested are significant with a value of <0.50. Of the five tested aspects, the highest score was in the empathy aspect of 16.89 percent and the lowest score was in the reliability aspect, which was 1.99 percent. Overall all aspects studied are significant to visitor satisfaction. Therefore, the high quality of service is directly proportional to the high visitor satisfaction.